History has become a trump card: historical research and the climate crisis in Southeast Asia - Klinken, Gerry van (Universitas Negeri Malang, 2023)
The climate crisis is above all a human crisis, not simply a technical one. Are the sciences of the humanities ready to offer intellectual leadership? This paper makes three suggestions for Indonesian historians to take a guiding role in bringing about a better, more sustainable, happier future for all Indonesians. The first is to write new kinds of histories. Material environmental histories could focus on deforestation and the petroleum industry. Cultural environmental histories could highlight traditional ecological knowledges that once flourished in villages that are today considered “backward.” The second suggestion is to engage in some of the biggest debates the country has ever had about how to achieve a more sustainable future. All these debates are really historical in nature, but only historians have the knowledge to offer a long-term perspective on them. The third suggestion is to dare to be imaginative – to dream of utopias, and not simply to report “facts” as if we ourselves were not part of them. Krisis iklim terutama sekali adalah krisis kemanusiaan, bukanlah krisis teknis. Apakah ilmu-ilmu humaniora siap memberikan kepemimpinan intelektual? Makalah ini mengajukan tiga saran bagi sejarahwan/wati Indonesia yang ingin berperan aktif menawarkan masa depan yang lebih bahagia kepada keluarga besar Indonesia. Yang pertama adalah, tulislah sejarah dalam bentuk baru. Sejarah lingkungan hidup material dapat menyoroti pembabatan hutan atau industri minyak. Sejarah LH budaya bisa fokus kepada kearifan ekologis tradisional di pedesaan dulu, tempat yang kini dianggap “terbelakang.” Saran kedua adalah: terjunlah ke dalam perdebatan paling dahsyat yang akan terdengar di Indonesia, yaitu bagaimana kita dapat mencapai masa depan yang berkelanjutan. Perdebatan ini pada intinya berpijak pada sejarah, dan hanya sejarahwan yang memiliki pengetahuan yang berwibawa untuk bicara tentang jangka panjang. Saran ketiga: beranikanlah diri untuk berimajinasi – untuk bermimpi tentang utopi, tidak hanya melaporkan “fakta” seolah kita berdiri di luar fakta itu.